2021
DOI: 10.1021/acsanm.1c02986
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization-Induced Self-Assembly of Tea Polyphenols into Open-Mouthed Nanoparticles for Active Delivery Systems and Stable Carbon Bowls

Abstract: Polyphenol-based hollow nanoparticles have exhibited intriguing properties in drug delivery, catalysis, and energy storage, and the open-mouthed (bowl-shaped) structure is supposed to improve the performance of the nanoparticles by increasing the accessibility of the inner surface and the cavity. Up to now, cationic polymers, metal ions, and sacrificial templates are generally applied in the preparation of the polyphenol-based hollow nanoparticle, and these polyphenols are usually confined to tannin acid and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The total Myr in mCBM was measured by the Folin–Ciocalteu method . In brief, mCBM solution (0.5 mL, 1 mg/mL) was added to the freshly prepared Folin–Ciocalteu’s B reagents (10%, 2.5 mL), and the mixture was kept in the dark for 5 min at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total Myr in mCBM was measured by the Folin–Ciocalteu method . In brief, mCBM solution (0.5 mL, 1 mg/mL) was added to the freshly prepared Folin–Ciocalteu’s B reagents (10%, 2.5 mL), and the mixture was kept in the dark for 5 min at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The total Myr in mCBM was measured by the Folin−Ciocalteu method. 37 In brief, mCBM solution (0.5 mL, 1 mg/mL) was added to the freshly prepared Folin−Ciocalteu's B reagents (10%, 2.5 mL), and the mixture was kept in the dark for 5 min at 25 °C. Then, Na 2 CO 3 solution (7.5%, 2.0 mL) was added to the mixture and kept in the dark for 60 min at 25 °C.…”
Section: Synthesis Of Csbmentioning
confidence: 99%
“…Tea polyphenols, a kind of well-documented dietary polyphenols, have attracted much attention due to their anticancer, antioxidant, and anti-inflammatory activities. Inspired by their amphiphilicity, the nanocarriers derived from tea polyphenols are capable of readily interacting with a wide range of therapeutic agents including nucleic acid, proteins, and small molecules with good or poor water solubility. , In addition to the universal encapsulation ability of the tea polyphenol-based nanocarriers, research studies have proved that these nanocarriers exhibit intrinsic therapeutic effects including anticancer, ,,,, antioxidation, and anti-inflammation. Our recent studies have established biosafe polyphenol-based nanoplatforms with the scale-up preparation and versatile nanodrug delivery systems of tea polyphenol nanoparticles (TP-NPs). ,, The inornate TP-NPs with intrinsic ROS scavenging and inflammation suppressing activities will be ideal drug delivery candidates in the development of nanomedicines for oxidative stress and inflammation-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…28−30 Inspired by their amphiphilicity, the nanocarriers derived from tea polyphenols are capable of readily interacting with a wide range of therapeutic agents including nucleic acid, 31 proteins, 24 and small molecules with good or poor water solubility. 23,32−38 In addition to the universal encapsulation ability of the tea polyphenol-based nanocarriers, research studies have proved that these nanocarriers exhibit intrinsic therapeutic effects including anticancer, 24,27,34,36,39 antioxidation, and anti-inflammation. 40−42 Our recent studies have established biosafe polyphenol-based nanoplatforms with the scale-up preparation and versatile nanodrug delivery systems of tea polyphenol nanoparticles (TP-NPs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…27 Previous studies reported simple approaches for preparing tea polyphenol nanoparticles for improved chemical stability and bioavailability. [28][29][30][31] Recently, a catechin-loaded nanogel with enhanced photoprotection and decreased UV-induced oxidative damage was developed. 32 It is worth mentioning that a single natural source is rarely applied to achieve broadband UV prevention because its actual narrow UV absorption range and low UV transmittance thereof achieved are far from satisfactory.…”
Section: Introductionmentioning
confidence: 99%